A mosquito mediator of parasite-induced immune priming. Issue 9 (September 2015) - Simões, Maria L.; Dimopoulos, George
<x xml:space="preserve">Abstract</x> Immune memory is a central feature of the mammalian adaptive immune system. The more primitive innate immune system of insects has also been shown to comprise memory, or immune priming. A recent study has shed new light on how Plasmodium primes the mosquito immune system for greater resistance to a subsequent infection with the same pathogen.